2007
DOI: 10.1149/1.2791947
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromism of Sn-Modified WO[sub 3] Electrodes Prepared from Sol-Gel Method

Abstract: Effects of SnO 2 addition on the structural, electrochemical, and electrochromic properties of WO 3 electrodes were investigated, in which both the WO 3 and SnO 2 -WO 3 were synthesized via a sol-gel method. The SnO 2 -WO 3 composite electrode, whose chemical states were identified through X-ray photoelectron spectroscopy analysis, gave the optical modulation of 38.3-99.5% and faster response times of 0.7 and 3.3 s. The coloration efficiencies of the SnO 2 -WO 3 electrode were greater ͑49.7 cm 2 C −1 ͒ by 14% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The electrochemical and optical properties of the electrospun WO 3 NWs prepared on the ITO-coated glass substrates were investigated and compared with that of thin film WO 3 electrode which was prepared on the ITO-coated glass by the conventional sol-gel process [26,27]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical and optical properties of the electrospun WO 3 NWs prepared on the ITO-coated glass substrates were investigated and compared with that of thin film WO 3 electrode which was prepared on the ITO-coated glass by the conventional sol-gel process [26,27]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Researches on metal doping have been performed on Nb, [20] Mo, [17] Ni, [46,47] Ti, [48] Ru, [49] V, [50] Ce, [51] and Sn, [52] and the results have shown that WO 3 with metal doping can have superior properties in one way or another. [10] Researches on metal doping have been performed on Nb, [20] Mo, [17] Ni, [46,47] Ti, [48] Ru, [49] V, [50] Ce, [51] and Sn, [52] and the results have shown that WO 3 with metal doping can have superior properties in one way or another.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…In practice, considerable attention has been given to the metal‐doped WO 3 , expecting to further improve the coloration efficiency, reaction kinetics as well as optical modulation of WO 3 by introducing the metal ions with lower oxidizing capacity than the host WO 3 . Researches on metal doping have been performed on Nb, Mo, Ni, Ti, Ru, V, Ce, and Sn, and the results have shown that WO 3 with metal doping can have superior properties in one way or another . For example, the addition of Ti to WO 3 was reported to stabilize the structure and can significantly promote the cycling performance .…”
Section: Electrochromic Metal Oxidesmentioning
confidence: 99%
“…Doping with metal ions (such as Ni and Ti, among others) has been widely investigated as another strategy for making high-performance WO 3 electrochromic materials. [24][25][26][27] Bathe et al investigated the inuence of Ti doping on the electrochromic properties of WO 3 thin lms prepared by pulsed spray pyrolysis, and suggested that doping WO 3 with Ti induced a phase transformation from monoclinic to amorphous and a rough surface morphology, resulting in improvement in the cycle stability, charge storage capacity, and reversibility of the lms. 24 Cai et al prepared Ti-doped WO 3 lms with a hierarchical star-like structure by a hydrothermal method, where the star-like structure had a low charge-transfer resistance and ion diffusion resistance, leading to fast switching speed and high coloration efficiency.…”
Section: Introductionmentioning
confidence: 99%